2019
DOI: 10.3892/ijmm.2019.4085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acid‑sensing ion channel�1a attenuates acid‑induced activation of autophagy via a calcium signaling pathway in articular chondrocytes

Abstract: Acid-sensing ion channel 1a (ASIC1a), member of the degenerin/epithelial sodium channel protein superfamily, serves a critical role in various physiological and pathological processes. The aim of the present study was to examine the role of ASIC1a in the autophagy of rat articular chondrocytes. Autophagy was induced by acidic stimulation in rat articular chondrocytes and the extent of autophagy was evaluated via the expression levels of microtubule-associated protein 1 light chain 3II, Beclin1 and uncoordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…PcTx1, the peptide toxin obtained from spiders, is a gating modifier of ASIC1a and has been widely used to explore the functions of ASIC1a (Leng and Xiong, 2013). Our previous studies have confirmed that PcTx1 reversed the enhancing effect of extracellular acidification on ASIC1a protein and mRNA expression in articular chondrocytes (Gao et al, 2019;Wu et al, 2019). Similarly, the increased expression and membrane trafficking of ASIC1a induced by PDGF stimulation were inhibited by PcTx1 (Zuo et al, 2019).…”
Section: Drugsmentioning
confidence: 78%
See 2 more Smart Citations
“…PcTx1, the peptide toxin obtained from spiders, is a gating modifier of ASIC1a and has been widely used to explore the functions of ASIC1a (Leng and Xiong, 2013). Our previous studies have confirmed that PcTx1 reversed the enhancing effect of extracellular acidification on ASIC1a protein and mRNA expression in articular chondrocytes (Gao et al, 2019;Wu et al, 2019). Similarly, the increased expression and membrane trafficking of ASIC1a induced by PDGF stimulation were inhibited by PcTx1 (Zuo et al, 2019).…”
Section: Drugsmentioning
confidence: 78%
“…ASIC1a has been characterized as a potent proton sensor for detecting extracellular acidification in the peripheral tissues and brain (Cheng et al, 2018). Our previous studies have indicated that extracellular acidosis increases protein expression of ASIC1a in a pH-and time-dependent manner in rat articular chondrocytes (Dai et al, 2017;Gao et al, 2019;Zu et al, 2020). Moreover, it has been reported that ASIC1a expression is significantly increased in the articular cartilage of adjuvant arthritis (AA) rats (Zhou et al, 2015), the articular synovial fluid of which showed a low pH value compared to that of the non-arthritic rat synovial fluid (Zhou et al, 2018).…”
Section: Acidosis and Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 2 years, our research team has shown that activated ASIC1a induces autophagy, synovial invasion, and synovial inflammation by mediating calcium influx (Gao, Xu, Ge, & Chen, 2019; Niu et al, 2020; Zhang et al, 2020). Calpains are ubiquitous calcium‐activated cysteine proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, it is related to the development of acidosis due to the lactic acid accumulation caused by the adenovirus-mediated stimulation of glycolysis [28]. While intracellular pH decreases, acid-sensing ion channels become activated and induce calcium influx [70,71]. Another possible mechanism of intracellular calcium accumulation is calcium flow through tiny pores in the membrane and lysosomal exocytosis induced by adenoviral E4 protein [20].…”
Section: Adenovirus Controls Necrosis and Necroptosis With The Help Omentioning
confidence: 99%